2017
DOI: 10.1108/jpif-09-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Anti-persistence and long-memory behaviour of SAREITs

Abstract: Purpose The purpose of this paper is to provide empirical evidence on the long-memory behaviour of South African real estate investment trusts (SAREITs). Design/methodology/approach The study employs a battery of advanced techniques to examine the behaviour of returns of 29 SAREIT equities listed on the Johannesburg Stock Exchange. The authors analysed daily closing prices covering different periods up to 21 May 2016. The results provide support for long memory in majority of SAREIT returns. Findings The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the same vein, Ntuli and Akinsomi (2017) found that South African REITs are good return-enhancers with diversification benefits, which could encourage shrewd investors to consider its inclusion in their mixed asset portfolios. Another study conducted in South Africa by Ijasan, Tweneboah and Mensah (2017) showed evidence of anti-persistence in South African REIT returns. With the earlier authors' analysis of performance of REITs, the current study focuses on a new perspective of the SCP paradigm by unravelling the relationship of the structure, conduct and performance in the REIT industry in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In the same vein, Ntuli and Akinsomi (2017) found that South African REITs are good return-enhancers with diversification benefits, which could encourage shrewd investors to consider its inclusion in their mixed asset portfolios. Another study conducted in South Africa by Ijasan, Tweneboah and Mensah (2017) showed evidence of anti-persistence in South African REIT returns. With the earlier authors' analysis of performance of REITs, the current study focuses on a new perspective of the SCP paradigm by unravelling the relationship of the structure, conduct and performance in the REIT industry in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In the same vein, Ntuli and Akinsomi (2017) found that South African REITs are good return-enhancers with diversification benefits which could encourage shrewd investors to consider its inclusion in their mixed asset portfolios. Another study conducted in South Africa by Ijasan, Tweneboah and Mensah (2017) showed evidence of anti-persistence in South African REITs returns.…”
Section: Literature Reviewmentioning
confidence: 95%